Dramatik Plot Teater Dulmuluk Naskah Lakon Zahara Siti - Nugroho Notosutanto Arhon Dhony (Besaung : Jurnal Seni Desain dan Budaya, 2018)
Abstract Dulmuluk Theater starts from literary art (poetry reading). Syair Abdul Muluk was composed by a woman named Saleha, the younger sister of Raja Ali Haji Ibn Raja Achmad Ibn. The youngster Raja Ali Haji Fi Sabilillah, who reigned in Riau, the island of Penyengat Indra Sakti, was estimated in the 19th century. A letter between Raja Ali Haji and a judge in Batavia (now Jakarta) named Philippus Pieter Roorda Van Eijsinga. Along with the development of Syair Abdul Dulmuluk, it has now been written in the form of drama text in general. This research journal is a qualitative type using descriptive analysis. The Dramaturgy theory approach is used to explore scripts and performances. The dramatic plot of Gustav Freytag consists of (exposition, complications, climax, resolution and denoumen) also used to discuss and analyze the play. Related to these issues, there is a problem formulation, namely: how dramatic is Dulmuluk's theater plot in the play of Zahara Siti. Data collection method is done by observation, literature study, interview, and documentation.Keywords: Poetry, Drama Script, Dramatik Plot, Zahara Siti's play Abstrak Teater Dulmuluk bermula dari seni sastra (pembacaan syair). Syair Abdul Muluk dikarang oleh seorang wanita yang bernama Saleha, yaitu adik perempuan dari Raja Ali Haji Ibn Raja Achmad Ibn Yang dipertuan Muda Raja Ali Haji Fi Sabilillah yang bertahta di Negeri Riau pulau Penyengat Indra Sakti diperkirakan abad ke 19. Hal ini diketahui dari data surat-menyurat antara Raja Ali Haji dengan seorang hakim di Batavia (sekarang Jakarta) yang bernama Philippus Pieter Roorda Van Eijsinga. Seiring perkembanganya Syair Abdul Dulmuluk, kini telah ditulis dalam bentuk teks naskah drama pada umumnya. Jurnal penelitian ini merupakan jenis kualitatif menggunakan deskriftif analisis. Pendekatan teori Dramaturgi digunakan untuk menggali naskah dan pertunjukanya. Dramatik plot Gustav Freytag terdiri dari (eksposisi, komplikasi, klimaks, resolusi dan denoumen) juga digunakan untuk membahas dan menganalisis naskah lakonya. Terkait permasalahan tersebut maka terdapat rumusan masalah, yaitu: bagaimana dramatik plot teater Dulmuluk dalam naskah lakon Zahara Siti. Metode pengumpulan data dilakukan dengan cara observasi, studi pustaka, wawancara, dan dokumentasi.Kata kunci : Syair, Naskah Drama, Dramatik Plot, Lakon Zahara Siti.